An Energy Efficient Data Gathering Protocol for Wireless Sensor Networks - Abhishek Bhattacharyya; Mrinal K. Naskar; Ayan Acharya; Anand Seetharam (Journal of Applied Computer Science & Mathematics, 2008)
Wireless sensor nodes, being highly energyconstrained, formulating energy-efficient protocols in orderto enhance network lifetime are of prime importance inwireless sensor networks. The LEACH and PEGASISprotocols which are elegant solutions to this problem try tominimize the overall energy dissipation by the nodes in thenetwork. While the LEACH protocol randomizes clusterheads for achieve equal energy dissemination, the PEGASISprotocol forms a chain of cluster heads taking rounds intransmitting to the base station. In this paper we propose anenergy efficient protocol which enhances the performance ofLEACH, PEGASIS. As the individual nodes are deployedrandomly in the area under surveillance the base station islocated at variable distances from them Thus each nodeactually dissipates a different amount of energy during itsturn of transmission to the base station. This energydifference between the various nodes keeps on increasingwith resulting in poorer network performance. In ourscheme each node only communicates with a close neighborand takes turns in transmitting to the base station dependingon its distance from it. This helps to iron out the unequalenergy dissipation by the individual nodes of the networkand results in superior performance as compared to LEACHand PEGASIS. Extensive simulations have been carried outwhich shows that significant improvement is over theseschemes.